Mitigating stigma associated with recycled water. Issue 3 (7th October 2021) - Ellis, Sean F.; Savchenko, Olesya M.; Messer, Kent D.
Abstract: Stigmatization of water and food products can constrain markets and prevent the implementation of scientifically safe solutions to environmental problems, such as water scarcity. Recycled water can be a cost‐effective, dependable, and safe solution to water shortages. However, consumers generally either require a large reduction in price to purchase products made with recycled water or reject such products outright. If emerging sustainable agricultural technologies, such as recycled water, are to be used to address growing water shortages worldwide, policymakers, water managers, and industry stakeholders must identify effective strategies for mitigating the stigma associated with recycled water. Using field experiments involving 1420 adult participants, we test the effectiveness of two stigma‐mitigating techniques. We also demonstrate a novel twist to the collection of representative samples in non‐hypothetical field experimental settings and then compare the results to a more traditional field experiment that recruited participants at large public gatherings. The analysis of these two different samples suggests a common finding: passing recycled water through a natural barrier, such as an aquifer, removes the stigma consumers would otherwise attach to it. We also find that the trophic level an organism occupies in the food chain influences stigmatizing behavior. The greater the steps in the food chain between an organism and the use of recycled water, the less it is stigmatized by consumers. These results have important implications for efforts to promote large‐scale potable and non‐potable water recycling projects and the use of recycled water in the agricultural industry.